Results of prospective multicenter study on heart failure on Campania Internal Medicine wards: the FASHION study - Fernando Gallucci; Ilaria Ronga; Andrea Fontanella; Generoso Uomo; and the FASHION Study Group (Italian Journal of Medicine, 2017)
Heart failure (HF) is characterized by a high prevalence and hospitalization rate with considerable health and social impact; the knowledge of its epidemiological features remains the mainstay to assess adequacy of the health care needs. The aim of this study was to evaluate the prevalence of HF in Internal Medicine Units of the Campania region (Italy) and patients’ characteristics. We recruited all patients with HF admitted between April 1 and June 30, 2014, in 23 Units of Internal Medicine: 975 patients (19.5% of 5000 admissions), 518 women and 457 men, mean age 76.9±9.9 (range 34-100) with 741 (76%) older than 70 years. The mean age was higher in women than men; 35.8% of patients had atrial fibrillation, with higher prevalence in women than in men. Coronary artery disease represented the leading etiology while prevalence of non-ischemic heart failure was higher in women. New York Heart Association class was indicated in 926 patients. Left ventricular ejection fraction (LVEF) was measured in 503 patients; 18.4% of patients had a severely reduced LVEF<35%, mostly men (P=0.0001) and 67.4% presented a LVEF>40%. At least one hospital admission in the previous 12 months was registered in 39.6% of patients. One, two and more than two relevant comorbidities were present in 8.6%, 24.7% and 64.8% of patients, respectively. Arterial hypertension and coronary artery disease were more frequent in female. In conclusion, advanced age and clinical complexity were the main characteristics of HF patients hospitalized in the Internal Medicine Units in Campania. Gender differences also emerged from the analysis of demographic parameters and etiopathogenetic features. Some diagnostic and therapeutic aspects not in line with that recommended by the most recent HF international guidelines were registered.